Ad-Dunya ka al-Ladzati Adhgatsi Ahlam (ad-Dirasah as-Simiyaiyah fi Syi’ri Abi al-‘Atahiyah) - Abdul Latif (Jurnal Internasional Pendidikan Bahasa Arab, 2021)
The poem al-Ladzatu Adhgatsu Ahlam was born from the pen of the Abbasid poet, Abu 'Atahiyah. This poem tells about some pleasures of false dreams, but the meaning of the pleasures of false dreams in this poem is still scattered in the poems. Michael Riffaterre's semiotic theory works to find the unity of meaning in a poem. Therefore, in this study the researcher used Michael Riffaterre's semiotic theory. The descriptive qualitative method was used by the researcher to analyze this poem. This study concludes that the unity of meaning in this poem is centered on the matrix of this poem, namely zuhud to facing the life. The model or monumental sentence in this poem was Ya nafsi kuni 'ani ad-dunya muba'idatan wa la tal'abanna bika ad-dunya wa khud'atuha. The actual hypogram behind this poem is found in surah al-Ankabut verse 64 and the potential hypogram of this poem is the world and wealth, life in this world is only temporary, and that humans should not prioritize the life of this world over the life of the hereafter.